LH and FSH promote migration and invasion properties of a breast cancer cell line through regulatory actions on the actin cytoskeleton. (5th December 2016) - Sanchez, Angel Matias; Flamini, Marina Ines; Russo, Eleonora; Casarosa, Elena; Pacini, Simone; Petrini, Mario; Genazzani, Andrea Riccardo; Simoncini, Tommaso
Abstract: Reproductive hormones influence breast cancer development and progression. While the actions of sex steroids in this setting are established, tentative evidence suggests that follicle-stimulating hormone (FSH) and luteinizing hormone (LH) may also play a role, yet this remains elusive. We here identify that T-47D breast cancer cells express functional receptors for FSH and LH, and that these hormones regulate breast cancer cell motility and invasion through the control of the actin cytoskeleton and the formation of cortical actin aggregates and focal adhesion complexes. Such actions are mediated by the cytoskeletal controllers Moesin and focal adhesion kinase (FAK). Moesin is recruited rapidly by FSH and LH through a signaling cascade requiring the G protein Gα13 and the Rho-associated kinase, ROCK-2. FSH and LH activate FAK via a Gαi /β and c-Src-dependent signaling cascade. Both cascades involve signaling to phosphatidylinositol-3 kinase and Akt. FSH and LH receptors and the related signaling intermediates are necessary for the actions of gonadotrophins on breast cancer cell cytoskeletal rearrangement, migration and invasion. These findings provide original information on the actions of gonadotrophins on breast cancer cells and may have clinical implications for the use of drugs that modulate gonadotrophins in breast cancer patients.